2013
DOI: 10.1177/1420326x13481048
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of thermal comfort adaptation behaviour in office buildings in the UK

Abstract: Around 40% of total energy consumption in the UK is consumed by creating comfortable indoor environment for occupants. Occupants' behaviour in terms of achieving thermal comfort could have a significant impact on a building's energy consumption. Therefore, understanding the interactions of occupants with their buildings would be essential to provide a thermal comfort environment that is less reliance on energy-intensive heating, ventilation and air-conditioning systems, to meet energysaving and carbon emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Accordingly, participants expressed a preference for personal devices providing directed thermal output. This corresponds to the findings of a study on adaptation behaviour, which found that adjustments on a personal, local level, such as clothing are preferred by office workers over adjustments on a more global scale (Liu et al 2014). Aesthetic and physical properties of wearable devices gain particular relevance once they are perceived as accessories or garments and the boundary to clothing and fashion is crossed and are key to the adoption of wearables (Wei 2014).…”
Section: Discussion Of Key Findingssupporting
confidence: 80%
“…Accordingly, participants expressed a preference for personal devices providing directed thermal output. This corresponds to the findings of a study on adaptation behaviour, which found that adjustments on a personal, local level, such as clothing are preferred by office workers over adjustments on a more global scale (Liu et al 2014). Aesthetic and physical properties of wearable devices gain particular relevance once they are perceived as accessories or garments and the boundary to clothing and fashion is crossed and are key to the adoption of wearables (Wei 2014).…”
Section: Discussion Of Key Findingssupporting
confidence: 80%
“…7 (Figure 11). This also demonstrates that thermal comfort is "a highly negotiable socio-cultural construct" [27] and that real-time feedback can prompt occupants' adaptive behaviour and reshape their notion of comfort. This process of redefining occupants' notion of comfort can contribute to lower building heating and cooling energy consumption.…”
Section: The Effects Of Feedback On Psychological Variablesmentioning
confidence: 80%
“…[23]. Many recent studies [24][25][26][27] In particular, the literature highlights that occupants' perceived ability of environmental control is a key psychological variable in defining occupants' thermal expectations [21,[28][29][30][31]. High perceived levels of control have been found to positively influence both thermal satisfaction [28,32,33] and productivity [34].…”
Section: The Dynamic Model Of Thermal Adaptationmentioning
confidence: 99%
“…In a naturally ventilated building, the temperature at which workers feel neutral can be predicted using the outdoor temperature because workers show environmentally adaptive behaviours such as clothing adjustments and the opening or closing of windows. 3 Liu et al 4 pointed out that occupants habitually make frequent personal adjustments for different environments, and their adaptive responses are thermally, socially and habitually conditioned. Geun et al 5 showed that the comfort temperature of occupants varies with season.…”
Section: Introductionmentioning
confidence: 99%